Characteristics and Classified Governance Strategies of Medium and Small Estuaries in Guangdong - CHEN Ying; WANG Shijun; HE Yong (Renmin Zhujiang)
This paper adopted the methods of field investigation,remote sensing analysis,and sedimentary dynamic analysis,summarized the characteristics of medium and small estuaries in Guangdong Province,and analyzed the main problems in the ecological governance of the estuaries.In addition,the paper studied typical experience in governing medium and small estuaries both in China and abroad and proposed classified governance strategies for medium and small estuaries.The results show that:①Medium and small estuaries in Guangdong Province are mainly divided into sandbar-lagoon estuaries,tidal channel estuaries,and drowned valley estuaries.Specifically,sandbar-lagoon estuaries are widely distributed.Tidal channel estuaries are mainly distributed in the west of Guangdong Province,and drowned valley estuaries can be found in the Leizhou Peninsula,the east coast of Shenzhen,and the east of Huizhou.②Medium and small estuaries face some problems,such as imperfect flood control systems,fragmented management,ineffective regional ecosystem service functions,and defective policies and systems for the construction of Lingnan water culture and the excavation,protection,and utilization of water heritage.③The paper proposed overall strategies of coordinated land and maritime development and systematic governance for medium and small estuaries as well as classified governance strategies for different estuaries and rivers,and the research results can provide some reference for the governance of medium and small estuaries in Guangdong Province.